Clinical behaviour, pathological findings, survival and prognostic factors in young woman in comparison to menopausal women with epithelial ovarian malignancy - Mokhtarudin, Rusinahayati; Vallipuram, Sivanesaratnam; Pailoor, Jayalakshmi; Mohd Nordin, Noraihan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Objective: The purpose of this study was to evaluate the clinical behaviour, pathological findings, survival and prognostic factors in young women in comparison to menopausal women with epithelial ovarian malignancy. Methods: A retrospective analysis of 141 patients (67 for age below 40 years and 74 menopausal) treated between 1980 and 2000 was conducted. Results: Irrespective of the stage, the most common clinical presentation was abdominal distension in both young (78%) and menopausal women (66%). In young women, 52% presented at an early stage of the disease and in menopausal women this was seen in 22% (p-value <0.05). The most common histological type of carcinoma in young women was mucinous cystadenocarcinoma (36%) and in menopausal women, it was serous cystadenocarcinoma (47%) (p<0.05).The overall 5-year survival rates in each group were 54% in young women and 41% in menopausal women. The 5-year survival rate appeared to be influenced by the stage of disease and tumour debulking surgery from univariate analysis in both young and menopausal women. In the final multivariate Cox proportional hazard model analysis, the optimal tumour debulking surgery was a significant (0.25; 95% CI (0.1-0.3) p <0.01) independent prognostic factor for survival probability in both young and menopausal women Conclusion: There are limited reports in the literature comparing the outcomes of younger and menopausal women with epithelial ovarian malignancy treated by any gynaecology oncologist from a single academic institution. Our results showed that the proportion of epithelial ovarian malignancy in young women was 30% from the total identified numbers of patients treated for epithelial ovarian malignancy. Although different types of carcinoma occurred in the young and menopausal women, the stage of the disease at presentation and optimal debulking surgery are important prognostic factors to ensure better survival rate.